Ozone as a novel emerging technology for the dissipation of pesticide residues in foods–a review - Pandiselvam, R.; Kaavya, R.; Jayanath, Yasendra; Veenuttranon, Kornautchaya; Lueprasitsakul, Piraya; Divya, V.; Kothakota, Anjineyulu; Ramesh, S.V. (Trends in food science & technology, 2020)
Consumption of fruits and vegetables is an indispensable component of human dietary preference, however; it is unfortunate that the enormous pesticide residues remain in the plant produces. Pesticides used to control the pests and diseases of the crops and livestock and its spill-over in the food production system has been an inevitable consequence. Researchers have been taking persistent efforts to eliminate pesticide residues in the food to make it safe for human consumption. Conventional techniques such as the washing of agricultural produces with chemicals, peeling, salting, and using different agents have not been an efficient means of pesticide removal. In recent times, the emergence of non-thermal technology such as the ozone to degrade the pesticide residues is of great utility in the food processing industries. It is also considered as a green technology because unlike other conventional methods ozone treatment leaves little residual traces. However, some of the discrepancies and challenges in using this technology require to be addressed to increase its efficiency. The objective of the current review is to provide a comprehensive and critical view of the use of ozone in pesticide residue dissipation in various food matrixes. Analysis of the pros and cons of ozone treatment reveals it as a potential technique for the degradation of pesticide residues. The diversity and complexity of pesticides along with the inherent differences in their chemical structures and residue levels of pesticides in agro-products are the factors that require due consideration. Furthermore, processing and operating conditions of the ozone treatment are some of the other major determinants to improve the efficiency of ozone treatment for the degradation of pesticides. •The concept of application of ozone in degrading the pesticide residues introduced.•Ozone-based dissipation of pesticides in food matrix for quality agro-products.•Challenges and prospects of ozone in food industry are enumerated.